2017
DOI: 10.1080/21541248.2017.1304855
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Rho GTPases and PI3K in the neutrophil

Abstract: Neutrophils are short-lived, abundant peripheral blood leukocytes that provide a first line of defense against bacterial and fungal infections while also being a key part of the inflammatory response. Chemokines induce neutrophil recruitment to inflammatory sites, where neutrophils perform several diverse functions that are aimed at fighting infections. Neutrophil effector functions are tightly regulated processes that are governed by an array of intracellular signaling pathways and initiated by receptor-ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Inhibiting GTPase prenylation results in the loss of several cellular functions including the modification of the cytoskeleton and binding to osseous surfaces culminating in the inhibition of osteoclastogenesis as well as the induction of apoptosis 22 . We hypothesize that these same mechanisms are likely to manifest within the neutrophil, as previous reports demonstrate a loss of PMN chemotactic and NADPH oxidase activity in the setting of GTPase prenylation inhibition 21 . In fact, previous work by our group has demonstrated that decreases in Rho GTPase activity are associated with impaired PMN migration 27 , 28 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Inhibiting GTPase prenylation results in the loss of several cellular functions including the modification of the cytoskeleton and binding to osseous surfaces culminating in the inhibition of osteoclastogenesis as well as the induction of apoptosis 22 . We hypothesize that these same mechanisms are likely to manifest within the neutrophil, as previous reports demonstrate a loss of PMN chemotactic and NADPH oxidase activity in the setting of GTPase prenylation inhibition 21 . In fact, previous work by our group has demonstrated that decreases in Rho GTPase activity are associated with impaired PMN migration 27 , 28 .…”
Section: Discussionsupporting
confidence: 59%
“…As an integral member of the innate immune system, PMNs are recruited from the circulation and migrate through tissues along chemoattractant gradients to clear invading microorganisms via phagocytosis, degranulation, neutrophil extracellular trap (NET) release and reactive oxygen species (ROS) production 20 . Regulation of PMN chemotaxis and the aforementioned antimicrobial effector functions is dependent on the prenylation of several small GTPases which act as mediators of intracellular signalling pathways 21 . The downstream inhibition of these same GTPases in osteoclasts secondary to n-BP exposure is responsible for the desired inhibition of osteoclastic function via dysregulation of cytoskeletal organization, loss of ruffled borders and attenuation of vesicular trafficking of critical lysosomal enzymes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…A central mechanism of regulation is the lipid second messenger phosphatidylinositol‐(3,4,5)‐trisphosphate (PIP 3 ), produced by phosphoinositide 3‐kinase (PI3K) within the cell membrane . Without PIP 3 , neutrophils cannot generate stable polarity and migration .…”
Section: Rac‐gtpases and Their Gefs In Neutrophilsmentioning
confidence: 99%
“…18,20 A central mechanism of regulation is the lipid second messenger phosphatidylinositol-(3,4,5)-trisphosphate (PIP 3 ), produced by phosphoinositide 3-kinase (PI3K) within the cell membrane. 19,20 Without PIP 3 , neutrophils cannot generate stable polarity and migration. 21,22 PIP 3 localizes several Rac-GEFs and other signalling proteins to the plasma membrane and activates some directly, by binding to their PH domain.…”
Section: In Neutrophilsmentioning
confidence: 99%
“…They efficiently and quickly phagocytose opsonised and non-opsonised bacteria and yeasts, and produce reactive oxygen species and degranulate (releasing a range of potent proteases and cytotoxic compounds that are stored in their specialised granules) to kill the ingested microbes inside the phagosome. These dynamic functions are all subject to regulation by small GTPases (Table 1 and [15][16][17][18]). In the following we concentrate on the function of Rho and Rap small GTPases in leukocyte-endothelial cell interactions.…”
Section: Small Gtpases and Neutrophilsmentioning
confidence: 99%